UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA MATA PELAJARAN IPAS SISWA KELAS IV SDN TINGKIR TENGAH 01 - Vidya Fauzia Utami; Mawardi (STKIP Subang, 2024)
This study was motivated by the low critical thinking skills of students in class IV SDN Tingkir Tengah 01. This study aims to improve students' critical thinking skills using the Project Based Learning model. The research method used was Classroom Action Research. The implementation of the PTK was carried out for 2 cycles. This research design consists of several stages, namely planning stage (planning), action (action), observation (observation) and reflection (reflection). The research subjects were class IV students totaling 27 students. The instruments used include tests, observations and documentation. The results of improving students' critical thinking skills can be seen at each stage of the cycle. Students experienced an increase in cycle I reaching 67% classical completeness with 18 students who were complete and 9 students were not complete. Whereas in cycle II, the completeness increased to 81% with 22 complete students and 5 students who were not complete. Thus it can be concluded that by applying the Project Based Learning model can improve students' critical thinking skills on the IPAS learning in class IV SDN Tingkir Tengah 01.